The impact of biomass burning emissions on aerosol concentrations and depositions in the northern South China Sea region - Li, Jiawei; Zhang, Zhisheng; Tao, Jun; Pan, Yuepeng; Luo, Li; Han, Zhiwei (Frontiers in Environmental Science, 2023)
The impact of biomass burning (BB) emissions on concentrations and depositions of major aerosol components in the northern South China Sea (NSCS) region (105~115˚E and 15~21˚N) from December 2020 to April 2021 have been investigated by using the WRF-Chem model (Weather Research and Forecasting model coupled with Chemistry) in combination with aerosol compositions measurement at a mountain site in the Hainan Island of China. Model comparisons with observations in Hainan demonstrated a good skill of WRF-Chem in simulating aerosol components (PM2.5, black carbon: BC, organic matter: OM, sulfate, nitrate, and ammonium) in the NSCS region. The influences of BB emissions were significant on near-surface PM2.5, BC, and OM but nearly negligible on secondary inorganic components (i.e., sulfate, nitrate, and ammonium). The NSCS regional and period mean PM2.5, BC, and OM concentrations were 17.2 μg/m3, 0.65 μg/m3, and 6.7 μg/m3, in which 20%, 13%, and 35%, respectively, were from BB emissions. At the meantime, the mean PM2.5, BC, and OM deposition fluxes were 73.8 mg/m2/month, 2.9 mg/m2/month, and 29.3 mg/m2/month, respectively, and 22%, 15%, and 38% of these depositions were from BB emissions. Dry deposition dominated the removal of aerosols. For both aerosol concentrations and depositions, the influences of BB emissions exhibited apparently larger contributions in spring (March and April) than those in winter (December to February). Most of the BB emissions were from Mainland Southeast Asia (MSEA), in terms of period mean, 79%, 72%, and 81% of the BB PM2.5, BC, and OM concentrations and 82%, 77%, and 83% of their depositions in the NSCS region were attributed to the MSEA region. The results of this study suggested that BB emissions have strong implications for air quality and biogeochemical cycle of the NSCS region.